Effectiveness of Kinesio Taping versus Mulligan’s Mobilization with Movement in Sub-acute Lateral Ankle Sprain in Footballers: A Randomized Controlled Trial - Abdul Qadeer Khan; Samraiz Mughal; Tooba Asif; Muneer, Maira; Sehar, Hurriya; Tariq, Umema (International Health Review, 2023)
The current study aimed to compare the effectiveness of Kinesio Taping (KT) and Mulligan Mobilization with Movement (MWM) in conjunction with conventional physical therapy for sub-acute lateral ankle sprain in football players. For this purpose, a total number of 30 participants were randomly assigned to either the KT group or the MWM group. Furthermore, pain, disability, and functional capabilities were assessed using the Numeric Pain Rating Scale (NPRS) and the Foot and Ankle Ability Measure (FAAM) before and after a 4-week intervention. The results showed that MWM with conventional physical therapy was more effective in relieving pain and improving mobility, strength, and functional status as compared to KT with conventional physical therapy. The study also suggested that MWM is a more beneficial treatment for footballers with a sub-acute lateral ankle sprain.